Ash deposition characteristics on heating surface in biomass circulating fluidized bed boiler. Issue 3 (14th September 2022) - Zhang, Dongwang; Deng, Boyu; Zhou, Tuo; Huang, Zhong; Yang, Hairui; Zhang, Man; Li, Shiyuan
ABSTRACT: A mathematical model of biomass ash deposition based on inertial impaction, thermophoresis deposition, and condensation was established to predict the ash deposition on the heating surface in a biomass boiler. Compared with the conventional numerical simulation methods, the mathematical models established are more focused on important design parameters in industry and can quickly calculate changes in parameters such as ash and heat flux density of heating area, and the simulated values were in good agreement with the measured results of the actual boiler. The growth of ash deposition on the heating surface of the boiler under different operating conditions was calculated by MATLAB program. The results show that the deposition caused by inertial impaction is dominant among the three deposition mechanisms. While the deposition caused by condensation is the least, accounting for only about 1%. The heat flux is only 1/2 of the initial stage when the ash deposition reaches a steady state. The ash deposition degree increases with the increasing of flue gas velocity, flue gas temperature, and particle size. When the flue gas temperature increases from 923 K to 1123 K, the ash deposition thickness increases from 7.6 mm to 14.2 mm. When the particle size increases from 12 μm to 20 μm, the thickness of ash deposition increases from 5.3 mm to 10.7 mm; when the gas velocity increased from 6 m/s to 15 m/s, the thickness of ash deposition increased from 6.5 mm to 10.6 mm. The ash depositions in two corn stalk-fired pure-combustion circulating fluidized bed (CFB) boilers were calculated, and the predicted results of the model were consistent with the actual ash deposition level.